Yiddish writers in Weimar Berlin: a fugitive modernism - Caplan, Marc (German Jewish Cultures Ser., 2021)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Introduction: Weimar and Now -- Part I. Spectral Empires: Landscapes, Nation-States, and the Homelessness of Weimar Modernism -- 1. A Past Become Space: Alfred Döblin and Dovid Bergelson in Poland, the Soviet Union-and Berlin -- 2. At the Crossroads of the Twentieth Century: Neue Sachlichkeit and Dovid Bergelson's Berlin Stories -- Part II. Melancholic Conspiracies: Masks, Masques, and Baroque Aesthetics in Yiddish and German Modernism -- 3. Watch the Throne: The Baroque, the Gothic, and Symbolism in Der Nister's Early Stories -- 4. Harold Lloyd and the Hermit: Popular Culture, Gothic Aesthetics, and the End of Der Nister's Symbolist Career -- Part III. Apocalyptic Origins: The Politics of Nostalgia in German and Yiddish Modernism -- 5. Arrested Development: Fragmentation, Apocalypse, and the Pursuit of Origins in Joseph Roth's Representation of Eastern Europe -- 6. Moyshe Kulbak's Berlin Writings: Here, There, Everywhere (Nowhere) -- Conclusion: Origin Is the Goal -- Selected Bibliography -- Index -- About the Author.